Continuous Flow Homolytic Aromatic Substitution with Electrophilic Radicals: A Fast and Scalable Protocol for Trifluoromethylation. Issue 1 (2nd December 2016) - Monteiro, Júlia L.; Carneiro, Paula F.; Elsner, Petteri; Roberge, Dominique M.; Wuts, Peter G. M.; Kurjan, Katherine C.; Gutmann, Bernhard; Kappe, C. Oliver
Abstract: We report an operationally simple and rapid continuous flow radical C−C bond formation under Minisci‐type reaction conditions. The transformations are performed at or below room temperature employing hydrogen peroxide (H2 O2 ) and dimethylsulfoxide (DMSO) as reagents in the presence of an Fe II catalyst. For electron‐rich aromatic and heteroaromatic substrates, C−C bond formation proceeds satisfactorily with electrophilic radicals including . CF3, . C4 F9, . CH2 CN, and . CH2 CO2 Et. In contrast, electron‐poor substrates exhibit minimal reactivity. Importantly, trifluoromethylations and nonafluororobutylations using CF3 I and C4 F9 I as reagents proceed exceedingly fast with high conversion for selected substrates in residence times of a few seconds. The attractive features of the present process are the low cost of the reagents and the extraordinarily high reaction rates. The direct application of the protocol to dihydroergotamine, a complex ergot alkaloid, yielded the corresponding trifluoromethyl ergoline derivative within 12 seconds in a continuous flow microreactor on a 0.6 kg scale. The trifluoromethyl derivative of dihydroergotamine is a promising therapeutic agent for the treatment of migraines. Abstract : The fast and the trifluoromethylation : Radical C−C bond formation with CF3 I, H2 O2, dimethylsulfoxide and Fe II as catalyst yields trifluoromethylated products within seconds in a continuous flow microreactor. The reaction proceeds satisfactorily with selected electrophilic radicals, including . C4 F9, . CH2 CN and . CH2 CO2 Et. The protocol allowed the trifluoromethylation of dihydroergotamine on a 0.6 kg scale.